1348Childhood adversities and diurnal patterns of salivary cortisol in adulthood: two UK-based prospective cohort studies. (2nd September 2021) - Akasaki, Mifuyu; Hardy, Rebecca; Steptoe, Andrew
Abstract: Background: Dysregulation of diurnal cortisol patterns may mediate between chronic stress and health problems. Findings on the association of childhood adversities with adult cortisol, however, are equivocal, mainly due to low statistical power, sample selection, and unstandardised indices of cortisol. Methods: Participants were from Whitehall II study (n = 3434), and National Child Development Study (NCDS) (n = 2072). In Whitehall II, multilevel models were used to examine associations of retrospectively measured childhood adversities with two indices of diurnal cortisol patterns (awakening response and diurnal slope) at a median age of 65. In NCDS, regression was used to investigate associations of prospectively measured adversities with two measures of morning cortisol at the age of 44/45. We then regressed predicted values of cortisol from these models against count of adversities to examine dose-response effects. Results: The prevalence of reporting at least one adversity was 67.8% in Whitehall II, and 47.8% in NCDS. None of the individual adversities were associated with overall cortisol levels in either study. However, for each additional adversity, there was a 1% elevated awakening response (95%CI: 0.8% to 1.19%), and, among men only, a 1.2% lower cortisol level at awakening (-1.98 to -0.40) with flatter diurnal slope (0.1 to 0.1) in Whitehall II; and a 1.3% lower cortisol level (-1.78 to -0.70) at 3.75 hrs after awakening in NCDS. Conclusions: Experience of multiple childhood adversities may be associated with dysregulated salivary cortisol patterns later in life. Key messages: Accumulation of childhood adversities might be associated with dysregulated diurnal cortisol patterns in adulthood.